Efektifitas pijat oksitosin dengan penyuluhan teknik menyusui menggunakan leaflet terhadap produksi ASI pada ibu post partum primipara - Yushida Yushida; Evi Zahara (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Breast milk is the main source of nutrition for babies from birth until they are able to digest other nutritional sources after 6 months of age. Failure in the breastfeeding process is often caused by maternal factors, namely breastfeeding. Actions to facilitate milk production include the oxytocin massage method.Objective: The aim of the study was to analyze the effect of oxytocin massage compared to counseling on breastfeeding techniques using leaflets on the milk production of primiparous postpartum mothers.Methods: The study used a quasi-experimental study with a pretest-posttest design. The sample selection was accidental sampling with inclusion and exclusion criteria, which consisted of 30 postpartum mothers who were divided into 2 groups, 15 respondents were given oxytocin massage and 15 respondents were given leaflets. The data analysis method was univariate and bivariate using Paired T-test and Independent T-test.Results: The results showed that the oxytocin massage treatment had a p-value= 0.000 (p < 0.05) meaning that there was a difference between before and after treatment. The control group had a p-value= 0.432 (p > 0.05) meaning that there was no difference between before and after treatment. There was a significant difference between the treatment group compared to the control group.Conclusion: Oxytocin massage has a significant effect in increasing milk production in primiparous postpartum mothers. Oxytocin massage is more effective than counseling using leaflet media to increase breast milk production.